Seni Grafis : Visualisasi Aktivitas Pandai Besi di Nagari Sungai Puar dengan Teknik Relief Print - Rafiqi Rafiqi; Yofita Sandra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This final work aims to contribute to the preservation of local culture, as well as introducing graphic art as a means of telling stories and depicting community life, especially the activities of blacksmiths in Nagari Sungai Puar. Therefore, the author created a work entitled